Minangkabau mothers and daughters in contemporary "rantau" society; Regaining power with modified matrilineal principles and patriarchal "rantau" norms - Elfira, Mina (Wacana, Journal of the Humanities of Indonesia, 2023)
The action of pai marantau (emigrating) is usually associated with the Minangkabau, the world’s largest matrilineal society, and one of the most fervently Islamic societies in Indonesia – the country with the largest Muslim population in the world. Once, it was mainly men who migrated, but more recently, women have also been emigrating. One consequence of emigrating from the matrilineal heartland in West Sumatra is that women lose some of the privileges conferred by the matrilineal adat, especially those pertaining to inheritance. Using qualitative fieldwork methods and Kandiyoti’s theory of the patriarchal bargain (1988), this paper explores how these women reconstitute matriliny in the contemporary rantau – in the multi-cultural society of the mega-city of Jabodetabek – by modifying it, and negotiating the terms of patriarchal norms. By exploring the mother-daughter relationships of emigrant Minangkabau women, the conclusion is that they have successfully exercised their agency, adapting to social changes, and regaining their power by using modified matriliny, and taking advantage of patriarchal norms.